Optimalisasi Sanksi Administratif untuk Pelanggaran Izin Lingkungan dalam Rangka Mendukung Tujuan Pembangunan Berkelanjutan - Arman, Zuhdi; Syahril, Syahril (Jurnal Jejak Hukum Indonesia (JHI), 2024)
Administrative law enforcement plays a vital role in environmental management. This article analyzes the effectiveness of administrative sanctions as a legal instrument to address environmental permit violations. Using normative approaches and case studies, this article highlights the relevance of administrative sanctions implementation to achieving sustainable development goals (SDGs). The findings suggest that optimizing administrative sanctions can enhance corporate compliance with environmental regulations, provided it is supported by a transparent monitoring system and consistent law enforcement.